Physical Disability and Sexuality Stories from South Africa - Hunt, Xanthe; Braathen, Stine Hellum; Chiwaula, Mussa; Carew, Mark T.; Rohleder, Poul; Swartz, Leslie (Springer Nature, 2021)
This open access edited volume explores physical disability and sexuality in South Africa, drawing on past studies, new research conducted by the editors, and first-person narratives from people with physical disabilities in the country. Sexuality has long been a site of oppression and discrimination for people with disabilities based on myths and misconceptions, and this book explores how these play out for people with physical disabilities in the South African setting. One myth with which the book is centrally concerned, is that people with disabilities are unable to have sex, or are seen as lacking sexuality by society at large. Societal understandings of masculinity, femininity, bodies and attractiveness, often lead people with physical disabilities to be seen as being undesirable romantic or sexual partners. The contributions in this volume explore how these prevailing social conditions impact on the access to sexual and reproductive healthcare, involvement in romantic relationships, childbearing, and sexual citizenship as a whole, of people with physical disabilities in the Western Cape of the country. The authors' research, and first person contributions by people with physical disabilities themselves, suggest that education and public health policy must change, if the sexual and reproductive health rights and full inclusion of people with disabilities are to be achieved.